Green synthesis and characterization of silver nanoparticles from Acacia nilotica and their anticancer, antidiabetic and antioxidant efficacy. (1st July 2022) - Zubair, Muhammad; Azeem, Muhammad; Mumtaz, Rabia; Younas, Madiha; Adrees, Muhammad; Zubair, Errum; Khalid, Abdullah; Hafeez, Farhan; Rizwan, Muhammad; Ali, Shafaqat
Abstract: Both cancer and diabetes mellitus are serious health issues, accounting more than 11 million deaths worldwide annually. Targeted use of plant-mediated nanoparticles (NPs) in treatment of ailments has outstanding results due to their salient properties. The current study was designed to investigate the safe production of silver nanoparticles (AgNPs) from Acacia nilotica . Different concentrations of AgNO3 were tested to optimize the protocol for the synthesis of AgNPs from the bark extract . It was demonstrated that 0.1 M and 3 mM were found to be the optimum concentrations for the synthesis of AgNPs. Standard characterization techniques such as UV–vis spectrophotometry, SEM, SEM-EDX micrograph, spot analysis, elemental mapping and XRD were used for the conformation of biosynthesis of AgNPs. Absorption spectrum of plant-mediated AgNPs under UV–vis spectrophotometer showed a strong peak at 380 nm and 420 nm for AgNPs synthesized at 0.1 M and 3 mM concentration of salt. The SEM results showed that AgNPs were present in variable shapes within average particle size ranging from (20–50 nm). Anticancer, antidiabetic and antioxidant potential of green AgNPs was investigated and they showed promising results as compared to the positive and negative controls. Hence, AgNPs were found potent therapeutic agent against the human liver cancer cell lines (HepG2), strong inhibitor for α-glucosidase enzyme activity and scavenging agent against free radicals that cause oxidative stress. Further studies are however needed to confirm the molecular mechanism and biochemical reactions responsible for the anticancer and antidiabetic activities of the particles. Highlights: AgNPs were synthesized using A. nilotica bark extract. NPs were characterized with XRD, SEM-EDX, EDS spot analysis, Elemental mapping. Average size of NPs was < 24 nm with agglomerated and crystalline forms. NPs have anticancer, α-glucosidase inhibition activity and antioxidant potential.